2015
DOI: 10.1002/tox.22181
|View full text |Cite
|
Sign up to set email alerts
|

Altered hepatic mRNA expression of immune response-associated DNA damage in mice liver induced by potassium bromate: Protective role of vanillin

Abstract: Chronic exposure to potassium bromate (KBrO ), a toxic halogen existing widely in the environment, environment through contaminated drinking water, has become a global problem of public health. The present study investigates the protective role of vanillin against KBrO induced oxidative stress, distruption in inflammatory cytokines expression, DNA damage, and histopathological changes. Adult mice were exposed orally to KBrO (2g/L of drinking water) for 2 weeks The co-administration of vanillin to the KBrO -tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Coadministration of vanillin, a polyphenolic flavoring agent, to maneb-treated mice restored MDA, H 2 O 2 , and AOPP levels, without reaching control values. Similar findings have been found by Ben Saad et al, 46 where vanillin attenuates the increase in lipid peroxidation, AOPP, and protein carbonyl formation in the liver of mice treated with potassium bromate. Also, Kadeche et al 10 have reported that vanillin exhibits hepatoprotective effect against metribyzin pesticide toxicity in male Wistar rats.…”
Section: Discussionsupporting
confidence: 90%
“…Coadministration of vanillin, a polyphenolic flavoring agent, to maneb-treated mice restored MDA, H 2 O 2 , and AOPP levels, without reaching control values. Similar findings have been found by Ben Saad et al, 46 where vanillin attenuates the increase in lipid peroxidation, AOPP, and protein carbonyl formation in the liver of mice treated with potassium bromate. Also, Kadeche et al 10 have reported that vanillin exhibits hepatoprotective effect against metribyzin pesticide toxicity in male Wistar rats.…”
Section: Discussionsupporting
confidence: 90%
“…The protective effect of vanillin against KBrO 3 induced liver, bone, and blood disorders has also been investigated [58, 59]. Coadministration of vanillin to KBrO 3 -treated mice significantly prevented DNA damage, hepatic cell alteration, and plasma transaminases increases, inhibited hepatic lipid peroxidation, and attenuated depletion of enzymatic and nonenzymatic antioxidants and expression levels of proinflammatory cytokines, including tumor necrosis factor- α , interleukin-1 β , interleukin-6, and COX2.…”
Section: Antimutagenic Activitymentioning
confidence: 99%
“…For example, KBrO 3 is a carcinogen that can cause oxidative stress [ 118 ]. Although it was banned from the food processing industry, the presence of KBrO 3 in the environment has still harmed human health [ 119 ], largely via targeting the kidney and thyroid to induce tumorigenesis [ 120 ]. Classic antioxidant enzymes, such as superoxide dismutase (SOD) and catalase, have little protective effect on KBrO 3 -induced oxidative damage.…”
Section: The Roles Of Ipa In Host Diseases and Healthmentioning
confidence: 99%